An Investigation of the Neuronal Dynamics Under Noisy Rate Functions - Asaad, Renas Rajab (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: In latest years, it has been argued theoretically both by experiments and by numerical simulations that noise of ion channel in neurons effect on the dynamical behavior of neuron when the size of membrane area is limited. Different models that extend the Hodgkin-Huxley equations into stochastic differential equations to capture the effects of ion channel noise analytically have been put forward: the Fox-Lu model, the Linaro-Storace-Giugliano model, and the Güler model. Moreover, very recently it has been argued by Güler that the rate functions for the opening and closing of gates are under the influence of noise in small size neurons. In this thesis, the neuronal dynamics with subject to noise in the rate functions will be investigated thoroughly. The investigation will employ the exact Markov simulations and the above analytical models. Results from these models will be presented comparatively. The study aims at presenting a more detailed account on the phenomenon already outlined by Güler recently. Keywords: Ion Channels, Channel Noise, Colored Noise, The Channel Crossing, Small-sized Dice, Stochastic Hodgkin-Huxley. ………………………………………………………………………………………………………………………… ÖZ: Son yıllarda, nöronlardaki ion kanal gürültüsünün küçük boyutlu nöron dinamiği üzerinde hayati etki yapabildiği deneysel olarak ve sayısal benzetim yöntemleri kullanarak kanıtlanmıştır. Sözkonusu etkinin analitik olarak ifade edilmesine yönelik olarak farklı gruplar Hodgkin-Huxley denklemlerini stokastik diferansiyel denklem haline dönüştürmüştür: Fox-Lu (1994); Linaro, Storace ve Giugliano (2011); Güler (2013a). Daha yakın zamanda, Güler (2013b) tarafından geçit kapanım-açılım oran fonksiyonlarının gürültülü olabildiği öne sürülmüştür. Bu tezde, yukarıdaki stokastik Hodgkin-Huxley modelleri gürültülü oran fonksiyonları altında çalışılmıştır. Güler (2013a) modelinin diğer modellere göre mikroskopik benzeşim sonuçlarıyla çok daha uyumlu olduğu gözlenmiştir. Anahtar Kelimeler: İyon kanalı, Kanal gürültüsü, Renkli gürültü, Kanal geçiti, Küçük boyutlu zar, Stokastik Hodgkin-Huxley.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2014. Supervisor: Prof. Dr. Marifi Güler.
Keywords: Computer Engineering; Ion Channels, Channel Noise, Colored Noise, The Channel Crossing, Small-Sized Dice, Stochastic Hodgkin-Huxley